Operations research transforms the scheduling of chilean soccer leagues and south American world cup qualifiers - Alarcón, Fernando (2017)
For the past 12 years, the Chilean Professional Soccer Association (ANFP) has applied operations research (OR) techniques to schedule soccer leagues in Chile. Using integer programming-based methods, the ANFP decides which matches are played in each round, taking into account various objectives, such as holding down costs and ensuring engaging tournaments for the fans. It has scheduled more than 50 tournaments using this approach, resulting in an estimated direct economic impact of about $59 million, including reductions in television broadcaster operating costs, growth in soccer paytelevision subscriptions, increased ticket revenue, and lower travel costs for the teams. This application of OR has also had significant noneconomic impacts. First, the incorporation of team requirements and various sporting criteria has improved process transparency and schedule fairness, increasing fans' interest in local professional tournaments; second, because of the high portability of these techniques, they have been used successfully to schedule sports leagues in other countries (examples include volleyball and basketball in Argentina, and the South American qualifiers for the 2018 Soccer World Cup). Furthermore, the models and methods used in this scheduling application have been disseminated widely, helping to promote OR as an effective tool for addressing practical problems. Our outreach activities have reached thousands of high school and university students in four countries and a more general audience of millions of television viewers and Internet users.